2013
DOI: 10.1155/2013/763624
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Dissatisfaction Is Increased in Male and Overweight/Obese Adolescents in Botswana

Abstract: Introduction. The purpose of this study was to examine linkages between obesity, physical activity, and body image dissatisfaction, with consideration of socioeconomic status (SES) and urbanization in adolescents in Botswana. Materials and Methods. A nationally representative, cross-sectional survey in 707 secondary school students included measured height and weight to determine overweight (OW) or obesity (OB) using World Health Organization standards; physical activity (PA) using the International Physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 22 publications
1
25
1
3
Order By: Relevance
“…In this study, adolescents with excess weight had OR aj 1.27 (CI 95% : 1.03 to 1.58) more likely to perceive their health unsatisfactorily. These results are similar to those found in other studies 25,26 . Excess weight is associated with various adverse health outcomes caused by physical, social and emotional problems 27 .…”
Section: Authors' Contributionssupporting
confidence: 93%
“…In this study, adolescents with excess weight had OR aj 1.27 (CI 95% : 1.03 to 1.58) more likely to perceive their health unsatisfactorily. These results are similar to those found in other studies 25,26 . Excess weight is associated with various adverse health outcomes caused by physical, social and emotional problems 27 .…”
Section: Authors' Contributionssupporting
confidence: 93%
“…Rate of dissatisfaction was found high among overweight (44.9%) and obese (57.9%) in comparison with underweight (32.8%) and normal (20.7%) adolescents. A study conducted in Botswana in 2012 found greater dissatisfaction among overweight and obese in comparison with normal and underweight adolescents (7).…”
Section: Discussionmentioning
confidence: 99%
“…Underweight, overweight and obesity are well established factors for body image dissatisfaction among the adolescents. Several studies conducted in the developing countries have found a significant association of overweight and obesity with the body image dissatisfaction (7)(8)(9). Overweight and obese adolescents are often found to underestimate their body weight while underweight and normal adolescents over estimate their body weight (10).…”
Section: Introductionmentioning
confidence: 99%
“…The only study we could access suggests that overweight and obesity among adolescents in Botswana are associated with body image dissatisfaction. 8 This study included mainly girls (61%) from an urban area and the mean age of students was 14.9 years. 8 As such, more studies need to be done to investigate whether or not obesity is considered as physically attractive, particularly in the rural adult population of African countries.…”
Section: Introductionmentioning
confidence: 99%
“…8 This study included mainly girls (61%) from an urban area and the mean age of students was 14.9 years. 8 As such, more studies need to be done to investigate whether or not obesity is considered as physically attractive, particularly in the rural adult population of African countries. Such information may help to develop targeted interventions to tackle the growing overweight and obesity problems in Africa.…”
Section: Introductionmentioning
confidence: 99%